ANALISIS FRAMINGBERITA HARIAN UMUM SOLOPOS TENTANG KESETARAAN KAUM DIFABEL PERIODE JANUARI-MARET 2012 - ., priyono (KOMUNITAS, 2014)
This  research  based  on  the  author  interest  to  issue  equity  interest.  In  real  life  there  are  many  disability rights are not guaranteed to materialize despite a state regulation. While the role of the mass media or newspapers are still not optimal to voice disabilities equal rights as other citizens according to their needs. Object of this study is the Solopos news about the equality of disabled published during the period January to March 2012. Researched news  are  six  items.  The  research  aims  to  determine  the  framing  of  Solopos  daily  about  disability  equality.   The research use framing analysis method with the analysis of Zhodang Pan and Gerald M. Kosicki. News that has been  obtained  in  the  data  collection  were  analyzed  by  framing  device  of  Pan  Kosicki  consisting  of  four major structures, namely syntax, script, thematic and rhetorical. Analysis results were then compared with the data results of interviews with the managing editor, desk editorand field reporter. The results showed Solopos view disabilities as an important issue. Disabled people deemed equalrights with other citizens according to their needs. Everything related disabilities equality rights have protrusion certain aspects such as the appearance of the dominant issues of disability  equality  and  equality  assertion  supported  sources  in  Solopos  coverage.